Analisis Kinerja Aparatur Pemerintahan Dalam Penyaluran Program Keluarga Harapan (PKH) Pada Masyarakat Miskin Di Kelurahan Kenangan Baru Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Hutabarat, Anjuyto; Lubis, Yurial Arief; Suharyanto, Agung (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
The Family Hope Program (PKH) is a conditional cash transfer targeting Very Poor Families (KSM) with the aim of alleviating poverty. This article aims to analyze the performance of government officials in distributing PKH to the poor in Kenangan Baru Village and to find out what are the inhibiting factors in distributing PKH in the Village. The problem in this research is focused on the less than optimal distribution of PKH aid funds and also the target of receiving PKH assistance that has not been realized properly. In order to approach this problem, the theoretical reference from Mondy, Noe and Premeaux regarding performance measurement includes Quantity, Quality, Independence, Initiative, Adaptation, Cooperation. The data collected is based on data collection techniques through observation, interviews, and documentation. Then analyzed using a descriptive qualitative method. This study concludes that the quantity of work; PKH distribution has been carried out well, Quality of work; not yet precise target and timing of distribution of funds, the independence of the apparatus; have not been able to work with minimal help from others, Initiative; in response to data problems PKH companions visited KPM homes, Adaptation; PKH assistants adapt well to KPM in monthly activities, Cooperation; lack of coordination between assistants and apparatus in the Kelurahan. Obstacles in PKH distribution are not synchronized KPM data, lack of KPM participation in monthly activities, limited companion human resources, and undisbursed aid funds.